Multivariate analysis of Raman spectra of carbonaceous black drawing media for the in situ identification of historic artist materials. (8th July 2018) - Daly, Nathan S.; Sullivan, Michelle; Lee, Lynn; Trentelman, Karen
Abstract: The identification of black drawing materials in works of art on paper is often important for their conservation and crucial to gain insight about artists' methodologies and the historic use of drawing materials. Traditionally, conservators and curators have had to rely upon visual observation with multiple wavelengths of light and magnification to characterize the materials in drawings, a challenging task further complicated if the media have been manipulated by the artist. The use of carbon‐based pigments in black drawing materials, ranging from charcoals and chalks to pastels and crayons, can be verified in situ using Raman microspectroscopy based on the presence of the two broad spectral bands characteristic of carbonaceous materials. However, the subtle differences in these spectral features between pigments can be difficult to discern, especially in cases with high background fluorescence. Here, we utilized principal component analysis to distinguish a group of 14 reference black drawing materials, both contemporary and historic, in the Raman spectral region of 800–2, 000 cm −1 . The model generated successfully differentiates between charcoal, chalk, and fabricated stick media, with sensitivity to both the Raman bands of carbon‐based materials as well as the fluorescent background profile. We validated the model using Raman spectra of black media on 19th‐century French drawings from the J. Paul Getty Museum collection that were previously classified visually by microscopic evaluation. Abstract : We use principal component analysis to distinguish a group of reference black drawing materials, both contemporary and historic, based on their in situ Raman spectral response in the region of 800–2, 000 cm −1 . The model generated can successfully differentiate between charcoal, chalk, and fabricated stick media, with sensitivity to both the Raman bands of carbon‐based materials as well as the fluorescent background profile. We validate the model using seven 19th‐century French drawings from the J. Paul Getty Museum collection.